Basal forebrain and hippocampus as predictors of conversion to Alzheimer's disease in patients with mild cognitive impairment-a multicenter DTI and volumetry study - Brüggen, Katharina; Dyrba, Martin; Barkhof, Frederik; Hausner, Lucrezia; Filippi, Massimo; Nestor, Peter J.; Hauenstein, Karlheinz; Klöppel, Stefan; Grothe, Michel J.; Kasper, Elisabeth A.; Teipel, Stefan (Journal of Alzheimer's disease, 2015)
Background: Hippocampal grey matter (GM) atrophy predicts conversion from mild cognitive impairment (MCI) to Alzheimer’s disease (AD). Pilot data suggests that mean diffusivity (MD) in the hippocampus, as measured with diffusion tensor imaging (DTI)